(untitled) - Delaney, David (Cambridge, UK,New York, 2003)
Exploring the relationship between conceptions of nature and (largely American) legal thought and practice, this study focuses on the politics and pragmatics of "nature talk"--as expressed in extra-legal disputes as well as different forms of legal discourse. Topics include the forces of nature, endangered species, animal experiments and bestiality. David Delaney demonstrates throughout that nearly any analysis of "nature" entails an interpretation of the essence of "humanity"
Keywords: Science and law,Natural law,Law,Khoa học và luật pháp,Luật pháp; Philosophy,Triết học; United States,Hoa Kỳ